The Relationship of Exchange Rate Volatility and Indonesia's Export Proceeds from Country Partners - Puspawardhani, Maria Angelica; Khoirunurrofik, Khoirunurrofik (Budapest International Research and Critics University, 2021)
This study analyzes the impact of the risk of exchange rate volatility on export proceeds (DHE) as well as the relationship of partner countries to Indonesia's potential DHE receipts. This research using panel data method uses a monthly period from January 2012 to December 2018 with 38 types of commodities and 191 partner countries. This study reveals that the impact of exchange rate volatility has a negative effect, while high-income export partner countries have a positive effect on DHE receipts. This study supports the optimization of DHE acceptance policies in Indonesian banks to ensure the availability of foreign exchange supply. The impact of the risk of exchange rate volatility on DHE receipts can be anticipated by increasing the cooperation of more advanced and high-income partner countries.